Global impact of RNA polymerase II elongation inhibition on alternative splicing regulation - Ip, Joanna Y.; Schmidt, Dominic; Pan, Qun; Ramani, Arun K.; Fraser, Andrew G.; Odom, Duncan T.; Blencowe, Benjamin J. (Genome Research, 2011)
The rate of RNA polymerase II (Pol II) elongation can influence splice site selection in nascent transcripts, yet the extent and physiological relevance of this kinetic coupling between transcription and alternative splicing (AS) is not well understood. We performed experiments to perturb Pol II elongation and then globally compared AS patterns with genome-wide Pol II occupancy. RNA binding and RNA processing functions were significantly enriched among the genes with Pol II elongation inhibition-dependent changes in AS. Under conditions that interfere with Pol II elongation, including cell stress, increased Pol II occupancy was detected in the intronic regions flanking the alternative exons in these genes, and these exons generally became more included. A disproportionately high fraction of these exons introduced premature termination codons that elicited nonsense-mediated mRNA decay (NMD), thereby further reducing transcript levels. Our results provide evidence that kinetic coupling between transcription, AS, and NMD affords a rapid mechanism by which cells can respond to changes in growth conditions, including cell stress, to coordinate the levels of RNA processing factors with mRNA levels.
10.1101/gr.111070.110